The Role of the Ketapang Village Government In the Development of Califour BUMDes : Peran Pemerintah Desa Ketapang Dalam Pengembangan BUMDes Califour - Pramita, Emy Dewi; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2023)
This qualitative research study explores the role of the Ketapang Village Government in fostering the development of Village-Owned Enterprises (BUMDes) in the Tanggulangin subdistrict of Sidoarjo Regency, Indonesia. Employing a triangulation data collection method and utilizing Miles and Huberman's interactive analysis technique, the study identifies four key roles played by the Ketapang Village Government: regulator, dynamizer, facilitator, and catalyst. The results highlight the government's efforts in providing guidance, encouraging community participation, offering support through supervision and financing, and accelerating the village's potential development. The study reveals that supportive factors include the availability of facilities, specific policies on management, and guidance and supervision mechanisms, while a lack of environmental awareness, particularly in maintaining the cleanliness of the Affaour River, emerged as a significant challenge. These findings contribute to the understanding of effective governance in rural areas and hold implications for policymakers, researchers, and practitioners involved in rural development and community empowerment initiatives. Highlights: Role of Ketapang Village Government: Explores the multifaceted roles of the Ketapang Village Government in facilitating the development of Village-Owned Enterprises (BUMDes) and promoting rural development. Factors Influencing Implementation: Identifies the supportive factors, such as available facilities and guidance mechanisms, as well as the challenges related to environmental awareness in the context of BUMDes development. Implications for Policy and Practice: Offers insights for policymakers, researchers, and practitioners on effective governance strategies and community participation in rural areas to foster sustainable development and empower local communities. Keywords: Village-Owned Enterprises, Rural Development, Governance, Community Participation, Triangulation Method.